PERTANGGUNGJAWABAN HUKUM PENYEDIA LAYANAN KESEHATAN TERHADAP PEMENUHAN HAK PESERTA JAMINAN KESEHATAN NASIONAL - Nur Azizah Wulandari; Purwanto Purwanto; Erna Susanti (Jurnal Ilmiah Advokasi, 2025)
Healthcare is a constitutional right guaranteed by the 1945 Constitution of the Republic of Indonesia and various regulations in the field of health and social security. This study aims to analyze the legal accountability of hospitals in fulfilling the rights of participants in the National Health Insurance (JKN) program, with a case study at the Abdoel Wahab Sjahranie Regional General Hospital in Samarinda. This study uses a socio-legal approach with qualitative methods, which examines the relationship between health service regulations, administrative service practices, and the legal accountability mechanisms of hospitals in providing services to JKN participants. The results show that although hospitals have made efforts to fulfill their legal obligations and service standards, there are still gaps between legal norms and service practices, particularly in relation to administrative issues, infrastructure limitations, and handling complaints from JKN patients. The legal accountability of hospitals in practice is mostly manifested through administrative mechanisms and a tiered complaint system, but this does not fully guarantee the optimal protection of patient rights. This study emphasizes that strengthening human resource capacity, integrating service information systems, and effective regulatory oversight are important prerequisites for improving the legal accountability of hospitals and realizing fair, non-discriminatory, and sustainable health services. This study contributes to revealing the gaps in the implementation of hospitals' legal obligations in the JKN system and provides an evaluative basis for strengthening the protection of health insurance participants' rights.Keywords: health services; national health insurance; legal accountability; patient rights